2021
DOI: 10.3389/fmars.2021.717360
|View full text |Cite
|
Sign up to set email alerts
|

Summer Mortality Syndrome Affecting Cultured European Seabass at Kafrelsheikh Province, Egypt

Abstract: The present work aimed to investigate the causes of summer mortality syndrome affecting cultured European seabass (Dicentrarchus labrax) by examining physiochemical farm water characteristics, isolation, and identification of recovered bacterial pathogens from diseased fish studying the effect of water temperature on stress biomarkers and disease severity. Studied water parameters were normal except ammonia and dissolved oxygen was higher and lower than the standard value. Sixty-two bacterial isolates were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…In recent years, Egyptian tilapia farms have faced unusual mortality episodes, particularly during the summer season with high mortality rate and general signs of septicemia, which known as Summer Mortality Syndrome “SMS”. The phenomenon was firstly reported by Fathi et al, 2017 in tilapia farms, however, SMS has been used recently to describe unusual mortalities in marine fish, Cultured European Seabass (Ali et al, 2021). The same study has identified some bacterial pathogens ( Vibrio fluvialis , Pseudomonas aeruginosa , and Staphylococcus aureus ) from the affected fish.…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, Egyptian tilapia farms have faced unusual mortality episodes, particularly during the summer season with high mortality rate and general signs of septicemia, which known as Summer Mortality Syndrome “SMS”. The phenomenon was firstly reported by Fathi et al, 2017 in tilapia farms, however, SMS has been used recently to describe unusual mortalities in marine fish, Cultured European Seabass (Ali et al, 2021). The same study has identified some bacterial pathogens ( Vibrio fluvialis , Pseudomonas aeruginosa , and Staphylococcus aureus ) from the affected fish.…”
Section: Introductionmentioning
confidence: 96%
“…Vitek 2 Compact system (bioMérieux, France) was used for bacterial isolate identification using the Gram‐negative card according to the method described by Ali, El‐Nokrashy, et al. (2021). The biochemical profile of each isolate was determined at different time points and then automatically matched with the system database.…”
Section: Methodsmentioning
confidence: 99%
“…Cortisol was extracted as described by Ali, El‐Nokrashy, et al. (2021); plasma cortisol was assayed by measuring the absorbance at 415 nm in a microplate reader model AO, Azure Biosystems, USA, using the Cayman cortisol determination kit, USA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diseased fish show the general signs of septicemia (Ali et al, 2018). Ali et al (2021b) reported that thermal stress is the main predisposing factor for the summer mortality syndrome associated with disease outbreaks affecting cultured fish, stressed fish became immune-compromised and highly susceptible to bacterial diseases. resistance (Baiano and Barnes, 2009).…”
Section: Introductionmentioning
confidence: 99%